FORM, METHODS AND MEANS OF FORMING CHILDREN'S MUSICAL ABILITY - Khojageldieva Mahfuza Ergash kizi; Eshmurodova Durdona Uktamovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The Center for Music and Rhythm is a very interesting center. In this, children can enter the characters they want, sing songs if they want, and play music on musical instruments if they want. This center can also be used as a corner. But using it as a center gives more positive results.